THE POLITENESS STRATEGIES USED IN THE Q INTERVIEW: ADELE OPENS UP ABOUT 30 - Atmawijaya, Tito Dimas; Efryanti, Amelia (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
The goal of this research was to investigate the politeness strate that were utilized throughout the interview, which included exchanges that were capable of being examined with the help of the themes covered in this study. The video interview with Adele titled â€œThe Q Interview: Adele Opens Up about 30â€ (2021), which was uploaded to the Q channel on the CBC YouTube Channel, will serve as the focus of this investigation. In order to conduct an analysis of politeness strategies, the author followed the guidelines provided by P. Brown and S. C. Levinson (1987) and their theory. In this study, qualitative research methodologies were employed to produce an analysis, which was then either written or illustrated. According to the findings of this research, both the host and the guest star utilized four distinct sorts of politeness strategies when delivering their respective utterances. These strategies included off-record, bald on-record, positive politeness, and negative politeness respectively. Payoffs and circumstances were among the other elements that had a role in shaping their statements. During the course of the interview, the type of politeness strategy that was most used is positive politeness. In addition, the factors that most influenced them were payoffs and social distance factors